2017
DOI: 10.2298/abs160308102s
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids in mature green and ripe red fruits of tomato (Solanum lycopersicum L.) grown under different levels of irrigation

Abstract: The effect of water deficit on concentrations of carotenoids was investigated in ripening tomatoes using HPLC-PDA. Fifteen different tomato cultivars were grown under three levels of water supply and unripe and fully-ripe fruits were harvested at different stages. Water deficit significantly affected several morphological and fruit yield-related parameters. In unripe tomato fruits, the relative concentrations of xanthophyll cycle carotenoids, e.g., violaxanthin and antheraxanthin, were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Obviously, the plants exposed to mild or moderate HS exhibited an increase in activity of the enzymatic antioxidant systems. Similar results were observed in plants exposed to other moderate environmental stresses, such as water [36,37] and salt stress [20].…”
Section: Discussionsupporting
confidence: 83%
“…Obviously, the plants exposed to mild or moderate HS exhibited an increase in activity of the enzymatic antioxidant systems. Similar results were observed in plants exposed to other moderate environmental stresses, such as water [36,37] and salt stress [20].…”
Section: Discussionsupporting
confidence: 83%
“…Increase of both sugars and organic acids could improve tomato fruit quality under water stress (Nahar et al, 2011). Different secondary metabolites, including carotenoids, are responsible for the nutrient and health values of tomato fruits and also are genotype-specific (Schweiggert et al, 2017). Comparison between cherry and large fruits showed that in both optimal and drought conditions fruits of cherry tomato had a higher total carotenoid content than large fruits, mainly due to higher content of lycopene and phytoene (Tables 4 and 5).…”
Section: Fruit Quality Of Cherry and Large Fruited Tomato Genotypes As Influenced By Water Deficitmentioning
confidence: 99%
“…In our current study, we observed that upregulated DE-lncRNA target genes and 2 DE-mRNAs were enriched in carotenoid biosynthesis, which is responsible for synthesising carotenoids during plant stress (Additional file 10 D, Additional file 9 C ). Based on this result, we conclude that WS increases carotenoid levels in rye and is potentially associated with the activation of the xanthophyll cycle [ 6 , 36 ].…”
Section: Discussionmentioning
confidence: 99%